Comparison of the Covid-19 Infection Severity in Known Diabetic Patients vs. Known Hypertensive Patients Admitted in A Tertiary Care Hospital in Peshawar - Muhammad Asghar, Munazza Khan, Sumaira Bakhtiar, Muhammed Shamoon, Afshan Hamid, Zafaruddin (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To compare the severity of COVID-19 infection among known diabetic and known hypertensive patients who were admitted in a tertiary care hospital in Peshawar, Pakistan. Methodology: A cross-sectional clinical study was conducted for comparison in diabetic vs hypertensive patients in the department of medicine of Lady Reading Hospital, Peshawar during the period from April-June 2021. All the patients were admitted in COVID ward and COVID ICU, showed their full consent and active participation in this study. Along with patient’s ECG and Echo report, a questionnaire based on Canadian categorization employed for angina grading and NYHA categorization to classify shortness of breath was used. Results: The mean age group taken for the sample was (n=140) with maximum age of 84 years. Majority were 102(72.9%) males and females were 38(27.1%). According to laboratory tests performed on patients of COVID-19 about 48(34.4%) of patients showed positive diabetes mellitus findings. Also, patients with positive hypertension found were 67(47.9%). The average stays of patients, at the hospital, was 15-40 days. About 58.3% of mortality was noted in patients with diabetes mellitus, a bulk of patients expired were from ICU-COVID-UNIT and 55.2% was the mortality rate in patients with positive hypertension according to our clinical findings and assessment. About 7.9% of COVID inpatients had cardiac infraction with severe condition and such patients who faced congestive heart failure expired. Almost 56(40%) of the patients were found with severe condition and 63(45%) were diagnosed with moderate condition during their stay at hospital. Conclusion: Regardless of age, gender and disease the death rate evaluated was 50%. Moreover, in diabetics and hypertensive patients there should be raised awareness for preventing the severity of disease. Keywords: COVID-19, Infection severity, Diabetic patients, Hypertensive patients, Tertiary care hospital, Pakistan